(untitled) (World Science, 2019)
The purpose of this article is the desire of the author, based on his previous multiple years’ experience in treating the effects of mTBI, as well as his experience in treating the effects of combat concussions, to offer, in addition to the methods already described, his own vision of how to deal with the problem at hand. The method proposed lies in complex application of manual therapy combined with shock wave therapy. Their combined power, when applied within a unified method of treatment, enhances the effect of each of them, creating a synergy that allows to achieve qualitatively better and significantly more successful clinical results.